2018
DOI: 10.1002/smi.2846
|View full text |Cite
|
Sign up to set email alerts
|

Nonmedical use of prescription drugs for cognitive enhancement as response to chronic stress especially when social support is lacking

Abstract: The nonmedical use of prescription drugs to improve cognitive performance has gained attention due to concerns over its social and political implications as well as side effects and long‐term health consequences. Some researchers expect a future trend of an instrumental use of drugs for cognitive enhancement (CE). Thus, getting insights about causes of CE‐drug consumption is warranted before the prevalence increases. Because perceived stress is ubiquitous in universities and may decrease cognitive performance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 77 publications
(202 reference statements)
2
33
0
1
Order By: Relevance
“…On the other hand, strengthening social support might alleviate mood disturbances. Social support has stress-buffering effects which reduce the probability of prescription medicine non-medical use (11). Besides, previous studies suggested that social support plays important roles in reducing the risk of substance use disorder formation and increasing the rate of successful cessation (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, strengthening social support might alleviate mood disturbances. Social support has stress-buffering effects which reduce the probability of prescription medicine non-medical use (11). Besides, previous studies suggested that social support plays important roles in reducing the risk of substance use disorder formation and increasing the rate of successful cessation (32).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reasons can contribute to the prescription medicine misuse, such as internal personality characteristics like self-e cacy and external environment in uence like social support (10)(11)(12). Therefore, the present study retrospectively analyzed the clinical characteristics of 61 subjects with methylphenidate use disorder who used oral administration.…”
Section: Introductionmentioning
confidence: 99%
“…University variables such as not having take‐home exams and having heavily weighted assessments came up as significant predictors, particularly for the use of prescription and OTC drugs as a CE in the past 12 months. The finding regarding take‐home exams may in part be explained by a recent systematic review which found that take‐home exams were associated with lower student anxiety in at least 10 studies [39] and previous research has noted that CE use has been associated with general [26] and university‐specific [27,30] stress. The finding that illicit drug use predicted the use of CEs in each category was also consistent with the existing literature [19,23,28,29] and unsurprising if one considers it may not be a large leap for those who use illicit drugs recreationally to see taking drugs to improve performance as just another instrumental use of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…There is then, a need for scholars to look beyond the 'West' and take a more global and comparative perspective to examine understandings of PCE and PCED consumption practices in varied socio-cultural and regulatory environments. Because PCDE use has often been connected to the pressure and stress in western educational institutions and workplaces (Bjønness, 2019, Steward & Pickersgill, 2019Krøll, 2019;Maier et al, 2018;Sattler, 2019), comparative work, analysing different settings and contexts, would help us gain a more nuanced knowledge about the phenomenon. We might also think of future work around pharmaceutical production and 'global supply chains' and how these act to shape consumption practices, to uncover and connect the production and manufacture of pharmaceuticalswhich often takes places within developing countrieswith their distribution, sale and use (Gabe et al, 2015).…”
Section: Summary and Future Agendasmentioning
confidence: 99%